Parental willingness to vaccinate their daughters against human papilloma virus and its associated factors in Woldia town, Northeast Ethiopia - Bittew, Sisay Melese; Masresha, Seteamlak Adane; Mulaw, Getahun Fentaw; Yimam, Mohammed Ahmed; Zimamu, Abiot Alebel; Abriham, Atnaf Alem; Kidie, Atitegeb Abera (Frontiers in Global Women's Health, 2024)
Background: The cells of the cervical epithelial wall are the source of the malignant tumor caused by the human papilloma virus known as cervical cancer. In 2018, Ethiopia implemented the human papillomavirus (HPV) vaccine specifically targeting girls aged 9 to 14 years old. This vaccination initiative serves as an effective preventive measure against cervical cancer, provided that parents express a positive inclination to have their daughters vaccinated as part of the program. Objective: To assess parental willingness to vaccinate their daughters against human papillomavirus and its associated factors in Woldia town, Northeast Ethiopia.A community-based cross-sectional study was conducted among 414 parents of daughters aged 9 to 14 years from January 10 to 25/2023. Respondents were selected by using a systematic sampling method and face-to-face interview was conducted to collect data. Data were entered by Epi data version 4.6 and exported to SPSS version 25 for analysis. Multivariable analyses were used to examine the association between dependent and independent variables. The adjusted odds ratio (AOR), 95% confidence interval, and p-value less than 0.05 were used to determine the statistical significance.Results: A total of 410 study participants with a response rate of 99% were included in the study, and about 72.9% [95% CI: 68.3%, 77.2%] of them were willing to vaccinate their daughters. This study found that parents having family history of cervical cancer screening [AOR=3.27 95%; CI=1.38, 7.74], secondary and above educational status [AOR=2.72, 95% CI= 1.29, 5.73], good knowledge of human papilloma virus vaccination [AOR=3.00, 95% CI= 1.70, 5.28], and favorable attitude towards human papilloma virus vaccine [AOR=4.40, 95% CI= (2.45, 7.88] were significantly associated with parental willingness to vaccinate their daughters against human papilloma virus.Recommendation: In this study, most parents were willing to vaccinate their daughters against human papilloma virus. The significant determinants of parental willingness to daughter's human papilloma virus vaccination were: family history of cervical cancer screening, level of education, knowledge and attitude towards human papilloma virus vaccine. Therefore, providing 3 health information regarding human papillomavirus vaccination with an emphasis to raise community awareness should be designed.